The twelve clues of Christmas [compact disc, unabridged] - Bowen, Rhys (Bowen, Rhys. Royal Spyness mysteries., 2014)
She may be 35th in line for the throne, but Lady Georgiana Rannoch cannot wait to ring in the new year before a Christmas killer wrings another neck.